QUO VADIS DESENTRALISASI PENDIDIKAN DI INDONESIA Tinjauan Historis, Orientasi dan Reformulasi Desentralisasi Pendidikan - Al Musanna; Syamsul Bahri (Universitas Islam Negeri Ar-Raniry, 2011)
Desentralization in education is a relatively new discourse in Indonesian national education. The contemporary political issues and indonesian government system, which is still searching for an ideal form of education after the falling down of the post-new order sentralistic government system, contribute to raise of this concept. Decentralization appears to be an alternative solution in managing a national education of Indonesia. It is expected that there will be more room for stakeholders through applying decentralization of education. Ideally, the desentralisation of education is intended as a commitment manifestation of policy makers on education in order to empower stakeholders, it is also to increase the accessibility and relevancy of education. The application of desentralization concept is can not be separated from political and sociological based-factors. This paper analyses the history and foundation of desentralization concept and it also analyses the problems that it causes.